Utilizing Opinion Leaders to Affect Goal Achievement for FYN Objectives - Robert Strong; Amy Harder (EDIS)
WC091, a 3-page fact sheet by Robert Strong and Amy Harder, informs Florida Yards & Neighborhoods coordinators how to identify and utilize opinion leaders to increase adult participation in their programs. Includes references. Published by the UF Department of Agricultural Education and Communication, January 2010.